Investigation of Membrane-Based Total Heat Exchangers with Different Structures and Materials - Zhong, Ting-Shu; Li, Zhen-Xing; Zhang, Li-Zhi (Journal of Membrane and Separation Technology, 2014)
Membrane-based total heat exchangers are devices to recover both sensible heat and latent heat from the exhaust air. The performances of exchangers assembled with different structures and membranes vary dramatically. To investigate performances, five modules are fabricated for comparison. A test rig is built to measure the performance of these total heat exchangers. The heat and moisture transfer in the cores are studied simultaneously. These cores can be divided into two categories: with different structures and with different membranes. For the first category, parallel-plates, plate-fins and cross-corrugated structures are used. For the second category, three kinds of membranes, i.e. one-step hand-made CA membrane, hydrophobic-hydrophilic composite membrane and machine-made CA membrane are used. The heat and mass transfer coefficients, sensible cooling and latent effectiveness are obtained through experimental measurements. The experimental results show that the cross-corrugated ducts can enhance heat and mass transfer effectively. And the one-step hand-made CA membrane has the lowest resistance in heat and moisture transfer.